Utilization of chico (Achras sapota) and tiessa (Pouteria camphechiana) in fruity muffin - Pancho, Portia Pauleth Osunero
Local nutritious fruits namely chico (Achras sapota) and tiessa (Pouteria camphechiana) were tested for fruity muffin production.